1999
DOI: 10.1074/jbc.274.32.22437
|View full text |Cite
|
Sign up to set email alerts
|

TIP49b, a New RuvB-like DNA Helicase, Is Included in a Complex Together with Another RuvB-like DNA Helicase, TIP49a

Abstract: We previously reported that TIP49a is a novel mammalian DNA helicase showing structural similarity with the bacterial recombination factor RuvB. In this study, we isolated a new TIP49a-related gene, termed TIP49b, from human and yeast cells. TIP49b also resembled RuvB, thus suggesting that TIP49a and TIP49b are included in a gene family. Like TIP49a, TIP49b was abundantly expressed in the testis and thymus. Enzyme assays revealed that TIP49b was an single-stranded DNAstimulated ATPase and ATP-dependent DNA hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
127
2
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(136 citation statements)
references
References 45 publications
5
127
2
2
Order By: Relevance
“…RUVBL2 was previously shown to be also required for the growth and survival of yeast. 7,31,32 Our data have shed some light on the mechanisms of apoptosis induced by RUVBL2 deficiency. We show that RUVBL2 down-regulation is associated with the increased conformational activation of the proapoptotic proteins Bak-1 and Bax.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…RUVBL2 was previously shown to be also required for the growth and survival of yeast. 7,31,32 Our data have shed some light on the mechanisms of apoptosis induced by RUVBL2 deficiency. We show that RUVBL2 down-regulation is associated with the increased conformational activation of the proapoptotic proteins Bak-1 and Bax.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, RUVBL2 has been found in supramolecular complexes that do not include ␤-catenin, 11 and ␤-catenin-independent functions of RUVBL2 have already been identified. 15 It is also noteworthy that RUVBL2 is required for the viability of yeast, 7,31,32 an organism devoid of ␤-catenin. In this context, 1 of the salient findings of this study was that in addition to its overexpression in HCC, RUVBL2 was also found in the cytoplasm of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The R2TP module RUVBL1 and RUVBL2 (RVB1 and RVB2; TIP49 and TIP48; pontin and reptin) RUVBL1 and RUVBL2 are ATPases of the AAA+ superfamily (ATPase associated with diverse cellular activities) and are related to the prokaryotic DNA helicase RuvB (Qiu et al 1998;Kanemaki et al 1999), which is involved in homologous recombination and doublestrand break repair (see Fig. 2 for a schematic representation of the R2TP module components).…”
Section: Introductionmentioning
confidence: 99%